Estudio de la construcción histórica y etnografía sobre las arepas de zapallo del Cantón Patate, Provincia de Tungurahua - Carvajal Núñez, Hector Bladimir (2021)
This research focuses on describing and analyzing the history, regarding the arepas of pumpkin and the way in which they affect the reconstruction of the gastronomic and cultural identity of the canton Patate, province of Tungurahua. Also, a high degree of acculturation is evidenced in the population of Patate and their identity in the process of cracking is evident. This study is descriptive, analytical and ethnographic with respect to the culture, tradition, history and gastronomy of the Patate canton, specifically of the arepas of pumpkin and the reasons for the disinterest of the new generations in their cultural legacy. The methods were used: historical, deductive-inductive and analytical, without neglecting the use of life histories and the review of archives. The application of the structured interview with 23 questions to a sample of 54 inhabitants, including foreigners and local authorities, was essential. The results of the present study include: the definition and analysis of the main reasons why the history and nutritional value of the pumpkin arepas of the Patate canton have been devalued. In addition, they include the strategies used and developed by the authorities and the populations for the conservation of the gastronomic and historical culture of the town. In the same way, the relevant information on the historical, demographic, cultural and gastronomic events of the inhabitants of the canton is evidenced, as well as the processes of making arepas, their ingredients and benefits.